Implementation of Geolocation and Jquery Latest For Salesman Monitoring in Android Based Applications - Ganda Yoga Swara; Putri Mandarani; G Giatman; S Syahril (IJISTECH (International Journal of Information System and Technology), 2021)
The purpose of this study is to design a sales activity monitoring application by utilizing the existing GPS on a smartphone. This research is an experimental research with the waterfall method. There are 5 stages in the waterfall method, namely requirements analysis, system design, implementation, integration & testing, operation & maintenance. Testing is done by testing the latest geolocation and jquery to see the success, failure or delay in the three test locations. The result of this research is that under the tree the highest success rate is 0.875, the lowest failure rate is 0.125 and the smallest delay (distance between data entry) is 0.45. The conclusion of this study is that the tracking system using Geolocation and the Latest jQuery if implemented in an open space with conditions under trees gets the highest rating compared to other test locations